2014
DOI: 10.1002/cphc.201402474
|View full text |Cite
|
Sign up to set email alerts
|

Triphenylamine Groups Improve Blocking Behavior of Phenoxazine Dyes in Cobalt‐Electrolyte‐Based Dye‐Sensitized Solar Cells

Abstract: Novel phenoxazine dyes are successfully introduced as sensitizers into dye-sensitized solar cells (DSCs) with cobalt-based electrolyte. In sensitizers with triphenylamine (TPA) groups recombination from electrons in the TiO2 conduction band to the cobalt(III) species is suppressed. The effect of the steric properties of the phenoxazine sensitizers on the overall device performance and on recombination and regeneration processes is compared. Optimized DSCs sensitized with IB2 having two TPA groups in combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…The PCEs of POZ-based dyes have achieved 7-8% [23][24][25]. It is a good method to modify the structures of the π-bridges at the molecular level to optimize the properties of organic dyes [26][27][28].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…The PCEs of POZ-based dyes have achieved 7-8% [23][24][25]. It is a good method to modify the structures of the π-bridges at the molecular level to optimize the properties of organic dyes [26][27][28].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Such a blocking effect of TPA groups was also recently observed for a series of phenoxazinebased dyes. [ 15 ] Charge extraction measurements (Figure 9 b) were performed to assess the effect of the sensitizer on the energy levels of the mesoporous TiO 2 electrode. Since no signifi cant difference is found, it may be assumed that the conduction band edge position of TiO 2 is not changed when sensitized with either D49 or E6 dye.…”
Section: Photovoltaic Performance Of Solar Cellsmentioning
confidence: 99%
“…Furthermore, we found that additional TPA groups on the donor part of a D-π-A dye gave good blocking effect on sensitizer. [ 12,15 ] Herein we design the synthesis and describe the utilization of a modifi ed triphenylamine (TPA) dye named E6 in which two external TPA donors via insulating aliphatic chains are introduced into donor part, in comparison to the parent dye molecule D49 , see Figure 1 . After photoinduced electron injection, positive charge from the center TPA group in E6 will move to an outer TPA unit, which will lead the charge further away from the TiO 2 surface.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, abundant dyes with D‐π‐A configuration have been successfully designed and synthesized by the researchers . Haid et al .…”
Section: Introductionmentioning
confidence: 99%